SOCIAL EMOTIONAL WELL-BEING OF HIGHER-SECONDARY STUDENTS - BHARTI, DAS AMBIKA; JHA, NANDANI (International Journal of Psychosocial Rehabilitation, 2019)
Well- being is one of the most important goals which individuals as well as societies strive for. Social emotional well-being is defined as the capacity to recognize and manage emotions, solve problems effectively and establish positive relationship with others. In present scenario efforts are made to make government educational institutions as strong as private in terms of facilitative environment for over-all development. The present study explored the social emotional well-being of higher secondary students from government and private schools. Purposive sampling method was used to draw 100 (N=100) higher secondary students from Bihar state. Out of the total sample 50 students were drawn from private school (n1=50) and another 50 from government schools (n2=50). Psychological wellbeing scale (Sisodia & Choudhary, 1971) was used to assess social emotional well-being in four dimensions, namely, satisfaction, efficiency, sociability, mental health and interpersonal relation. The findings suggest that the higher secondary students of private schools were significantly better in their overall social emotional wellbeing as well as its dimensions of mental health and interpersonal relationship when compared to their counterparts from government schools. The result has psychological implications for educational institutions.